PENERAPAN METODE PART AND WHOLE DALAM MENINGKATKAN MINAT SISWA PADA PEMBELAJARAN (PJOK) MELALUI PERMAINAN BOLA VOLY - Faizatul Widat; Misdur Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the application of the Part and Whole method in learning Physical Education, Sports and Health (PJOK) through volleyball at MI Nurul Mun'im. The Part and Whole method is applied by dividing basic volleyball skills, such as passing, serving and smashing, into simpler and separate parts, before combining them into a full game. This research uses a qualitative approach with a case study design, where data is collected through observation, interviews with teachers and students, as well as documentation of learning activities. Data analysis was carried out using a thematic analysis approach. The research results showed that the application of the part and whole method succeeded in increasing students' interest, involvement and technical skills. As many as 85% of students felt more confident and ready to take part in volleyball lessons after learning the basic techniques first, while 80% of students said they felt more interested and enthusiastic about practicing and 85 students were able to master the basic techniques of playing volleyball. Applying this method also creates a more enjoyable learning atmosphere and allows students to master basic techniques gradually. The implications of this research show that the Part and Whole method can be applied effectively to improve the quality of PJOK learning, especially in volleyball, by providing a more structured and enjoyable learning experience for students.